EXPERT SYSTEM MODELING FOR THE MULTIDIMENSIONAL EVALUATION OF AGED PEOPLE - Siqueira, Fernanda Matoso; Castro, Edna Aparecida Barbosa de; Carvalho, Dárliton Barbosa Feres; Trindade, Gabriel Santos; Cruz, Gylce Eloisa Cabreira Panitz; Mendonça, Érica Toledo de; Cavalcante, Ricardo Bezerra (Cogitare Enfermagem, 2023)
Objective: to describe the modeling of an Expert System for the Multidimensional Evaluation of aged people. Method: the study was carried out from April 2021 to September 2022 by researchers from universities in the inland of Minas Gerais - Brazil. The following stages were conducted: literature review; survey of the System requirements; modeling; and implementation. Results: the System makes it possible to assess the physical, psychosocial and functional aspects; it identifies the geriatric-gerontological needs and classifies them according to severity levels, in addition to offering suggestions for therapeutic interventions. The diverse information generated can be shared through instant messengers via apps, providing the basis for the development of a monitoring panel for aged people assisted in the municipality. Conclusion: the System presents itself as a technological solution given the importance of the multidimensional evaluation of aged people within the scope of care for this population segment and the lack of technological solutions to carry out the assessment.